Slope :
The slope or gradient of a line is a number that describes both the direction and the steepness of the line. (m = slope of the line)
Formula to find slope when two points are given :
m = (y2-y1)/(x2-x1)
Parallel lines :
If two lines are parallel,
m1 = m2
Perpendicular lines :
If two lines are perpendicular, then
m1 x m2 = -1.
m1 and m2 are slopes of first and second line respectively.
Find a given that the line joining :
Problem 1 :
A(1, 3) to B(3, a)
is parallel to a line with gradient 3.
Solution :
If two lines are parallel, then
Given, A(1, 3) to B(3, a)
Slope m1 = (y2 – y1)/(x2 – x1)
= (a -3)/(3 – 1)
= (a – 3)/2 ---(1)
Slope of the given line (m2) = 3 ---(2)
m1 = m2
(a – 3)/2 = 3
a – 3 = 6
a = 9
Problem 2 :
P (a, -3) to Q(4, -2) is parallel to a line with gradient 1/3.
Solution :
Given, P (a, -3)
to Q(4, -2)
= (-2
+ 3)/(4 – a)
m1 = 1/(4 – a) ----(1)
m2 = 1/3 ----(2)
m1 = m2
1/(4 – a) = 1/3
4 – a = 3
– a = 3 – 4
a = 1
Problem 3 :
M(3, a) to N(a,
5) is parallel to a line with gradient -2/5.
Solution :
Given, M(3, a) to
N(a, 5)
m1 = (5 –
a)/(a – 3) ----(1)
m1 = m2
m2 = -2/5 ----(2)
-2/5 = (5 – a)/(a – 3)
-2(a – 3) = 5(5 – a)
-2a + 6 = 25 - 5a
-2a + 6 – 25 + 5a = 0
-19 + 3a = 0
a = 19/3
a = 6 1/3
Find t given that the line joining :
Problem 4 :
A(2, -3) to B(-2, t) is perpendicular to a line with gradient 1 1/4.
Solution :
Since two lines are perpendicular then,
m1 x m2 = -1
Given, A(2, -3) to B(-2, t)
m1 = (y2 – y1)/(x2 – x1)
= (t + 3)/(-2 – 2)
= (t + 3)/-4
m1 x m2 = -1
(t + 3)/-4 x 1 1/4 = -1
(t + 3)/-4 x 5/4 = -1
(t + 3) x 5/-16 = -1
(t + 3) x 5 = 16
5t + 15 = 16
5t = 16 – 15
5t = 1
t = 1/5
Problem 5 :
C(t, -2) to D(1,
4) is perpendicular to a line with gradient 2/3.
Solution :
Given, C(t, -2)
to D(1, 4)
m1 = (y2 – y1)/(x2 – x1)
= (4 + 2)/(1 – t)
= 6/(1 – t)
m1 x m2 = -1
6/(1 – t) x 2/3 = -1
12/3(1 – t) = -1
12/3 – 3t = -1
12 = -1 x(3 – 3t)
12 = -3 + 3t
12 + 3 = 3t
15 = 3t
15/3 = t
5 = t
Problem 6 :
P(t, -2) to Q(5, t) is perpendicular to a line with gradient -1/4.
Solution :
Given, P(t, -2)
to Q(5, t)
m1 = (y2 – y1)/(x2 – x1)
= (t – (-2))/(5 – t)
= (t + 2)/(5 – t)
m1 x m2 = -1
(t + 2)/(5 – t) x -1/4 = -1
(-t – 2)/(5 - t)/4 = -1
(-t – 2)/(20 – 4t) = -1
-t – 2 = -20 + 4t
-t – 2 + 20 – 4t = 0
-5t + 18 = 0
t = 18/5
t = 3 3/5
Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 04, 25 08:16 AM
Feb 04, 25 08:15 AM
Feb 04, 25 08:11 AM